Palliative chemotherapy: The perspectives and experiences of south african nurses - Johanna Elizabeth Maree; Theola Potgieter (Elsevier, 2018)
Objective: The objective of this study was to describe the perspectives and experiences of South African nurses caring for patients receiving palliative chemotherapy. Methods: A qualitative descriptive design was used and purposive sampling allowed us to select 11 nurses practising in a private ambulatory cancer care center in Port Elizabeth. In-depth interviews, guided by three broad themes were conducted and analyzed using qualitative content analyses. Data saturation determined the sample size. Results: Two themes emerged from the data - the patients cling to hope and the positive influence of palliative chemotherapy. The participants believed that patients consenting to palliative chemotherapy were clinging to false hope. They were also of the opinion that family members pressurize patients to consent to treatment. The participants experienced palliative chemotherapy positively, especially when an improvement in the patients' quality of life or pain relief was evident. Fatigue was highlighted as the major side effect, but it did not temper the participants' positive attitudes toward the treatment. Conclusions: Although the participants believed that patients cling to hope and consent to palliative chemotherapy because they hope to be cured, they experienced the treatment as positive. For them, the improvement in pain and quality of life outweighed the side effects the patients experienced. The positive attitude patients upheld while receiving this treatment encouraged them. Nurses should gain more knowledge about the meaning, people living with advanced cancer, attach to hope to prevent them from interpreting patients' hope as denial and false.